Ta’zir Crimes in Islamic Criminal Law: Definition Legal Basis Types and Punishments - Lestari, Wilda (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2024)
This paper discusses the concept of Ta’zir Crimes in Islamic criminal law, which refers to criminal acts whose punishment is not clearly determined in the Qur’an and Hadith. Ta’zir crimes are different from hudud and qisas, where the punishment for violation is not expressly determined by the sharia, but rather left to the judge or authorized ruler based on the public interest and the principle of justice. This paper explains the definition, legal basis, types of ta’zir crimes and the various punishments that can be applied in this context. The legal basis for ta’zir crimes is taken from various sources, including verses of the Qur’an and the hadith of the Prophet that emhasize the importance of preventing crime and maintaining the public interest. The types of ta’zir crimes are explained based on the studied of Fuqaha who classify them into several catagories, depending on their nature and impact on society. In addition, this paper also describes the various types of punishments that can be imposed in ta’zir crimes, ranging from corporal punishment such as flogging and imprisonment to punishmentrelated to freedom and property. The overall discussion in this paper aims to provide a comprehensive understanding of the flexibility and relevance of ta’zir crimes in the context of enforcing Islamic law, as well as how sharia principles are applied in determining educative and preventive punishment.